Self-esteem and Social Intelligence in Visually Impaired Adolescents - Jawairia Saleem, Sadia Saleem, Sadia Ikram, Saima Inam, Asma Siddiqui, Qurat Ul Ain (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To explore the differences in the levels of self-esteem and social Intelligent in visually and non-visually impaired adolescents Study design: Cross sectional Place and duration: December, 2018 to February, 2020 in special education center private and government school of city Lahore Method: There were 122 people in total in the sample. There were 56 visually impaired volunteers and 66 non-visually impaired persons.Boys and girls aged 14 to 19 from private and public special education schools took part in the study. Two scales were used; Self-esteem Scale for Children (SESC), and Social Intelligence Scale (SIS) used along with a demographic Performa Results: Analysis revealed that being visually impaired and having low level of social facilitation is found to be a negative predictor of low self-esteem. There was no significant difference found on three factors of self-esteem and social intelligence. Overall visually impaired tend to have lower level of self-esteem. Conclusion: Adolescence is a vital period in a person’s life when he or she faces a number of psychological obstacles. If he had any type of handicap at this teenage time, he would have a lot of problems in his life. According to this study, if a person has any handicap throughout the teenage stage, it affects their degree of self-esteem and social intelligence. Key words: Self-esteem, Social Intelligence Visually Impaired, Non-Visually Impaired, Adolescents